Interventions on Costs and Survival Rates of Lung Cancer Patients - Fitriana Yuliastuti; Nurfina Dian Kartikawati; Missya Putri Kurnia Pradani; Cut Dewi Bunga; Roshan Kumar Mahato (Borneo Journal of Pharmacy, 2025)
Lung cancer is characterized by the uncontrolled growth of cells in the lung tissue, particularly in the lining of the respiratory tract. The disease has a high and alarming mortality rate, requiring prompt and appropriate management. This study aims to examine the costs and one-year survival rates of lung cancer patients at Dharmais Cancer Hospital. Data analysis was conducted in four stages: a retrospective observational study using secondary data from medical records, which described patient characteristics and factors affecting survival and treatment costs; analysis of survival curves by cancer stage and intervention; and testing differences in survival curves using the log-rank test. The results show that higher survival rates are often inversely proportional to shorter survival times, and vice versa. Stage 1 patients exhibited the most extended survival despite low survival rates for inpatients (48 months, 25%) and outpatients (53 months, 15%). Intervention types 4.00 (chemotherapy and radiotherapy) and 7.00 (chemotherapy, radiotherapy, and surgery) effectively extended survival, although associated survival rates remained low. The highest inpatient treatment costs were observed in stage 2 patients, while the highest annual outpatient costs were linked to surgical interventions, highlighting the difference between per-episode and cumulative annual expenditures.